Effect of pretransplant spleen volume on the prognosis of acute myeloid leukemia treated with allogeneic hematopoietic stem cell transplantation - Liu, Weiwei; Liu, Bingjie; Pang, Lihou; Zhou, Lixia; Wang, Fuxu; Zhang, Xuejun; Wang, Ying (Frontiers in Immunology, 2026)
ObjectiveThis study aimed to evaluate the influence of pre-transplant spleen volume on the prognosis of patients with acute myeloid leukemia (AML) undergoing allogeneic hematopoietic stem cell transplantation (allo-HSCT).MethodsWe evaluated 58 patients diagnosed with AML and who have undergone first allogeneic stem cell transplant at the Department of Hematology, Second Hospital of Hebei Medical University from 2017 to 2022. All patients were consecutively evaluated. Patients with AML evolving from myeloproliferative neoplasms (MPN) or secondary AML were excluded. Only de novo AML patients were included. The median follow-up time was 24 months, and the patients were categorized into non-enlarged spleen volume (NLSV) and large spleen volume (LSV) groups based on the spleen volume ranges of 120 normal individuals. A retrospective analysis was performed to evaluate the impact of spleen volume on post-allo-HSCT outcomes, including the incidence of infection, graft-versus-host disease (GVHD), relapse, overall survival (OS), and non-relapse mortality (NRM). Log-rank test was employed to compare survival curves, and a multivariable Cox regression model was utilized to assess spleen volume as a prognostic factor for long-term survival.ResultsAccording to the survival curve, the LSV group exhibited lower OS compared to the NLSV group (P=0.034), along with higher cumulative NRM (P=0.049) and lower relapse-free survival (P=0.023). No significant differences were observed in disease relapse, granulocyte engraftment, CMV infection, or GVHD incidence. The multivariable regression model confirmed spleen volume as a significant risk factor for OS, with cytomegalovirus (CMV) infection also influencing OS and NRM.ConclusionPre-transplant splenomegaly is independently associated with poor prognosis in AML patients.